Rare homozygous cilia gene variants identified in consanguineous congenital heart disease patients - Daniel A. Baird; Hira Mubeen; Canan Doganli; Jasmijn B. Miltenburg; Oskar Kaaber Thomsen; Zafar Ali; Tahir Naveed; Asif ur Rehman; Shahid Mahmood Baig; Søren Tvorup Christensen; Muhammad Farooq; Lars Allan Larsen (Human Genetics, 2024)
Congenital heart defects (CHD) appear in almost one percent of live births. Asian countries have the highest birth prevalence of CHD in the world. Recessive genotypes may represent a CHD risk factor in Asian populations with a high degree of consanguineous marriages. Genetic analysis of consanguineous families may represent a relatively unexplored source for investigating CHD etiology. To obtain insight into the contribution of recessive genotypes in CHD we analysed a cohort of forty-nine Pakistani CHD probands, originating from consanguineous unions. The majority (82%) of patient’s malformations were septal defects. We identified protein altering, rare homozygous variants (RHVs) in the patient’s coding genome by whole exome sequencing. The patients had a median of seven damaging RHVs each, and our analysis revealed a total of 758 RHVs in 693 different genes. By prioritizing these genes based on variant severity, loss-of-function intolerance and specific expression in the developing heart, we identified a set of 23 candidate disease genes. These candidate genes were significantly enriched for genes known to cause heart defects in recessive mouse models (P < 2.4e−06). In addition, we found a significant enrichment of cilia genes in both the initial set of 693 genes (P < 5.4e−04) and the 23 candidate disease genes (P < 5.2e−04). Functional investigation of ADCY6 in cell- and zebrafish-models verified its role in heart development. Our results confirm a significant role for cilia genes in recessive forms of CHD and suggest important functions of cilia genes in cardiac septation.

Finding the sweet spot: a qualitative study exploring patients’ acceptability of chatbots in genetic service delivery - Stephanie Luca; Marc Clausen; Angela Shaw; Whiwon Lee; Suvetha Krishnapillai; Ella Adi-Wauran; Hanna Faghfoury; Gregory Costain; Rebekah Jobling; Melyssa Aronson; Eriskay Liston; Josh Silver; et al. (Human Genetics, 2023)

A recessive variant in TFAM causes mtDNA depletion associated with primary ovarian insufficiency, seizures, intellectual disability and hearing loss - Farid Ullah; Waqar Rauf; Kamal Khan; Sheraz Khan; Katrina M. Bell; Vanessa Cristina de Oliveira; Muhammad Tariq; Shabnam Bakhshalizadeh; Philippe Touraine; Nicholas Katsanis; Andrew Sinclair; Sijie He; et al. (Human Genetics, 2021)

A missense allele of PEX5 is responsible for the defective import of PTS2 cargo proteins into peroxisomes - Muhammad Ali; Shahid Y. Khan; Tony A. Rodrigues; Tânia Francisco; Xiaodong Jiao; Hang Qi; Firoz Kabir; Bushra Irum; Bushra Rauf; Asma A. Khan; Azra Mehmood; Muhammad Asif Naeem; et al. (Human Genetics, 2021)

Biallelic loss-of-function variants in NEMF cause central nervous system impairment and axonal polyneuropathy - Ashfaque Ahmed; Meng Wang; Gaber Bergant; Reza Maroofian; Rongjuan Zhao; Majid Alfadhel; Marwan Nashabat; Muhammad Talal AlRifai; Wafaa Eyaid; Abdulrahman Alswaid; Christian Beetz; Yan Qin; et al. (Human Genetics, 2021)

Novel loss-of-function mutations in COCH cause autosomal recessive nonsyndromic hearing loss - Kevin T. Booth; Amama Ghaffar; Muhammad Rashid; Luke T. Hovey; Mureed Hussain; Kathy Frees; Erika M. Renkes; Carla J. Nishimura; Mohsin Shahzad; Richard J. Smith; Zubair Ahmed; Hela Azaiez; et al. (Human Genetics, 2020)

GPT2 mutations in autosomal recessive developmental disability: extending the clinical phenotype and population prevalence estimates - Qing Ouyang; Brian C. Kavanaugh; Lena Joesch-Cohen; Bethany Dubois; Qing Wu; Michael Schmidt; Ozan Baytas; Stephen F. Pastore; Ricardo Harripaul; Sasmita Mishra; Abrar Hussain; Katherine H. Kim; et al. (Human Genetics, 2019)

Variants in KIAA0825 underlie autosomal recessive postaxial polydactyly - Irfan Ullah; Naseebullah Kakar; Isabelle Schrauwen; Shabir Hussain; Imen Chakchouk; Khurram Liaqat; Anushree Acharya; Naveed Wasif; Regie Lyn P. Santos-Cortez; Saadullah Khan; Abdul Aziz; Kwanghyuk Lee; et al. (Human Genetics, 2019)

The contribution of parent-to-offspring transmission of telomeres to the heritability of telomere length in humans - Dayana A. Delgado; Chenan Zhang; Kevin Gleason; Kathryn Demanelis; Lin S. Chen; Jianjun Gao; Shantanu Roy; Justin Shinkle; Mekala Sabarinathan; Maria Argos; Lin Tong; Alauddin Ahmed; et al. (Human Genetics, 2019)

Novel candidate genes and variants underlying autosomal recessive neurodevelopmental disorders with intellectual disability - Regie Lyn P. Santos-Cortez; Valeed Khan; Falak Sher Khan; Zaib-un-Nisa Mughal; Imen Chakchouk; Kwanghyuk Lee; Memoona Rasheed; Rifat Hamza; Anushree Acharya; Ehsan Ullah; Muhammad Arif Nadeem Saqib; Izoduwa Abbe; et al. (Human Genetics, 2018)

Mutation in SLC6A9 encoding a glycine transporter causes a novel form of non-ketotic hyperglycinemia in humans - Majid Alfadhel; Marwan Nashabat; Hanan Al Qahtani; Ahmed Alfares; Fuad Al Mutairi; Hesham Al Shaalan; Ganka V. Douglas; Klaas Wierenga; Jane Juusola; Muhammad Talal Alrifai; Stefan T. Arold; Fowzan Alkuraya; et al. (Human Genetics, 2016)

A novel homozygous splicing mutation of CASC5 causes primary microcephaly in a large Pakistani family - Sandra Szczepanski; Muhammad Sajid Hussain; Ilknur Sur; Janine Altmüller; Holger Thiele; Uzma Abdullah; Syeda Seema Waseem; Abubakar Moawia; Gudrun Nürnberg; Angelika Anna Noegel; Shahid Mahmood Baig; Peter Nürnberg (Human Genetics, 2016)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Identification of a homozygous splice site mutation in the dynein axonemal light chain 4 gene on 22q13.1 in a large consanguineous family from Pakistan with congenital mirror movement disorder - Iltaf Ahmed; Kirti Mittal; Taimoor I. Sheikh; Nasim Vasli; Muhammad Arshad Rafiq; Anna Mikhailov; Mehrnaz Ohadi; Huda Mahmood; Guy A. Rouleau; Attya Bhatti; Muhammad Ayub; Myriam Srour; et al. (Human Genetics, 2014)

Truncation of the E3 ubiquitin ligase component FBXO31 causes non-syndromic autosomal recessive intellectual disability in a Pakistani family - Asif Mir; Kumudesh Sritharan; Kirti Mittal; Nasim Vasli; Carolina Araujo; Talal Jamil; Muhammad Arshad Rafiq; Zubair Anwar; Anna Mikhailov; Sobiah Rauf; Huda Mahmood; Abdul Shakoor; et al. (Human Genetics, 2014)

Characterization of a novel missense mutation in the prodomain of GDF5, which underlies brachydactyly type C and mild Grebe type chondrodysplasia in a large Pakistani family - Muhammad Farooq; Hiroyuki Nakai; Atsushi Fujimoto; Hiroki Fujikawa; Klaus Wilbrandt Kjaer; Shahid Mahmood Baig; Yutaka Shimomura (Human Genetics, 2013)

Genetic mapping of an autosomal recessive postaxial polydactyly type A to chromosome 13q13.3–q21.2 and screening of the candidate genes - Umm-e-Kalsoom; Sulman Basit; Syed Kamran-ul-Hassan Naqvi; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2012)

Studies in a consanguineous family reveal a novel locus for stuttering on chromosome 16q - Muhammad Hashim Raza; Rana Amjad; Sheikh Riazuddin; Dennis Drayna (Human Genetics, 2012)

An Alu repeat-mediated genomic GCNT2 deletion underlies congenital cataracts and adult i blood group - Guntram Borck; Naseebullah Kakar; Jochen Hoch; Katrin Friedrich; Jan Freudenberg; Gudrun Nürnberg; Rüstem Yilmaz; Shakeela Daud; Dost Muhammad Baloch; Peter Nürnberg; Johannes Oldenburg; Jamil Ahmad; et al. (Human Genetics, 2012)

Novel mutations in the keratin-74 (KRT74) gene underlie autosomal dominant woolly hair/hypotrichosis in Pakistani families - Naveed Wasif; Syed Kamran ul-Hassan Naqvi; Sulman Basit; Nadir Ali; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2011)

Autosomal recessive hyponatremia due to isolated salt wasting in sweat associated with a mutation in the active site of Carbonic Anhydrase 12 - Emad Muhammad; Neta Leventhal; Galit Parvari; Aaron Hanukoglu; Israel Hanukoglu; Vered Chalifa-Caspi; Yael Feinstein; Jenny Weinbrand; Harel Jacoby; Esther Manor; Tal Nagar; John C. Beck; et al. (Human Genetics, 2011)

DFNB89, a novel autosomal recessive nonsyndromic hearing impairment locus on chromosome 16q21-q23.2 - Sulman Basit; Kwanghyuk Lee; Rabia Habib; Leon Chen; Umm-e-Kalsoom; Regie Lyn P. Santos-Cortez; Zahid Azeem; Paula Andrade; Muhammad Ansar; Wasim Ahmad; Suzanne M. Leal (Human Genetics, 2011)

Identification of an autosomal recessive stuttering locus on chromosome 3q13.2–3q13.33 - Muhammad Hashim Raza; Sheikh Riazuddin; Dennis Drayna (Human Genetics, 2010)

Genetic mapping of a novel hypotrichosis locus to chromosome 7p21.3–p22.3 in a Pakistani family and screening of the candidate genes - Sulman Basit; Ghazanfar Ali; Naveed Wasif; Muhammad Ansar; Wasim Ahmad (Human Genetics, 2010)

Ectodermal dysplasia-cutaneous syndactyly syndrome maps to chromosome 7p21.1-p14.3 - Muhammad Tariq; Muhammad Nasim Khan; Wasim Ahmad (Human Genetics, 2009)

Gene structure and mutant alleles of PCDH15: nonsyndromic deafness DFNB23 and type 1 Usher syndrome - Zubair M. Ahmed; Saima Riazuddin; Sandar Aye; Rana A. Ali; Hanka Venselaar; Saima Anwar; Polina P. Belyantseva; Muhammad Qasim; Sheikh Riazuddin; Thomas B. Friedman (Human Genetics, 2008)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)

A syndromic form of autosomal recessive congenital microcephaly (Jawad syndrome) maps to chromosome 18p11.22–q11.2 - Muhammad Jawad Hassan; Muhammad Salman Chishti; Syed Muhammad Jamal; Muhammad Tariq; Wasim Ahmad (Human Genetics, 2008)

A mutation in the lipase H (LIPH) gene underlie autosomal recessive hypotrichosis - Ghazanfar Ali; Muhammad Salman Chishti; Syed Irfan Raza; Peter John; Wasim Ahmad (Human Genetics, 2007)

Autosomal recessive nonsyndromic deafness locus DFNB63 at chromosome 11q13.2–q13.3 - Shahid Y. Khan; Saima Riazuddin; Muhammad Tariq; Saima Anwar; Muhammad I. Shabbir; S. Amer Riazuddin; Shaheen N. Khan; Tayyab Husnain; Zubair M. Ahmed; Thomas B. Friedman; Sheikh Riazuddin (Human Genetics, 2007)

Phenotypic characterization of Bbs4 null mice reveals age-dependent penetrance and variable expressivity - Erica R. Eichers; Muhammad M. Abd-El-Barr; Richard Paylor; Richard Alan Lewis; Weimin Bi; Xiaodi Lin; Thomas P. Meehan; David W. Stockton; Samuel M. Wu; Elizabeth Lindsay; Monica J. Justice; Philip L. Beales; et al. (Human Genetics, 2006)

DFNB68, a novel autosomal recessive non-syndromic hearing impairment locus at chromosomal region 19p13.2 - Regie Lyn P. Santos; Muhammad Jawad Hassan; Shaheen Sikandar; Kwanghyuk Lee; Ghazanfar Ali; Protacio E. Martin; Michael Angelo L. Wambangco; Wasim Ahmad; Suzanne M. Leal (Human Genetics, 2006)

Localization of a novel locus for alopecia with mental retardation syndrome to chromosome 3q26.33–q27.3 - Peter John; Ghazanfar Ali; Muhammad S. Chishti; Syed Muhammad S. Naqvi; Suzanne M. Leal; Wasim Ahmad (Human Genetics, 2006)

A novel autosomal recessive non-syndromic hearing impairment locus (DFNB47) maps to chromosome 2p25.1-p24.3 - Muhammad Jawad Hassan; Regie Lyn P. Santos; Muhammad Arshad Rafiq; Maria H. Chahrour; Thanh L. Pham; Muhammad Wajid; Nadine Hijab; Michael Wambangco; Kwanghyuk Lee; Muhammad Ansar; Kai Yan; Wasim Ahmad; et al. (Human Genetics, 2006)

Linkage analysis identifies the thyroglobulin gene region as a major locus for familial congenital hypothyroidism - Bodil Ahlbom; Muhammad Yaqoob; Peter Gustavsson; Hafez Abbas; Göran Annerén; Agne Larsson; Claes Wadelius (Human Genetics, 2002)

Genetic and linkage analysis of familial congenital hypothyroidism: exclusion of linkage to the TSH receptor gene - B. Edman Ahlbom; Muhammad Yaqoob; Agne Larsson; Adam Ilicki; Göran Annerén; C. Wadelius (Human Genetics, 1997)